Diversity Status of Bamboo in Sumatra: A Review - Ritonga, Muhammad Azli; Syamsuardi, Syamsuardi; Nurainas, Nurainas; Damayanto, I Putu Gede P. (Universitas Gadjah Mada, 2024)
Prior to initiating the conservation effort, conducting a bamboo species inventory in a specific area is crucial for obtaining information about the diversity status of the species in that region. Species inventorying is a fundamental step in ensuring that conservation efforts are targeted, effective, and based on sound scientific data. Regrettably, status of bamboo diversity in Sumatra is unavailable. Therefore, a study was conducted to determine the status of bamboo diversity in Sumatra. The study gathered data from literature review. It covered bamboo species, their statuses (endemic, introduced, ex-situ conservation, and threatened), and encompassed the main Sumatra Island and surrounding smaller islands. Species were re-identified and validated. Conservation status was assessed based on IUCN categories. There are 73 species of bamboo in the Sumatra region, representing 10 genera: Bambusa (11 species), Chimonobambusa (1 species), Dendrocalamus (10 species), Dinochloa (2 species), Gigantochloa (26 species), Melocanna (1 species), Neololeba (1 species), Phyllostachys (1 species), Schizostachyum (19 species), and Thyrsostachys (1 species). Eighteen species of Sumatran bamboo are known as introduced species, and 30 species are endemic to Sumatra, with the majority belonging to Gigantochloa (15 species). The least represented are Bambusa and Dinochloa, each having one endemic species. Bambusa heterostachya, Dendrocalamus giganteus, and Dendrocalamus membranaceus fall into the “least concern” (LC) category on the IUCN Red List, while the remaining 70 species have not been evaluated. A total of 44 species have been planted (conserved) in botanical gardens in Indonesia, while the remaining 29 species have not yet been conserved.